Never intended to be a theory about everything: Domestic labour in neoclassical and Marxian economics - Jefferson, Therese; King, J. (Curtin University of Technology, 2001)
This article is a comparative study of the treatment of domestic labor by neoclassical and Marxian economists. Before 1960 mainstream economics concentrated on production for the market, with serious analysis of housework confined to a handful of economists, whose efforts in this regard were marginalized by economics departments but supported by departments of home economics. Later mainstream analyses, first in agricultural economics and then in human capital theory culminated in Gary Becker?s ?new household economics.? Domestic labor was also neglected by Marxist thinkers, who argued that housework was being socialized under capitalism and would disappear altogether under socialism, but it was rediscovered by Marxist-feminists in the late 1960s. Housework continues, however, to pose serious analytical difficulties for both neoclassical and Marxian economists.An ardent lover may decline a business interview in order to keep an appointment with his lady-love, but there will be a point at which its estimated bearing upon his prospects of an early settlement will make him break his appointment with the lady in favour of the business interview. A man of leisure with a taste for literature and a taste for gardening will have to apportion time, money, and attention between them, and consciously or unconsciously will balance against each other the differential significances involved. All these, therefore, are making selections and choosing between alternatives on precisely the same principle and under precisely the same law as those which dominate the transactions of the housewife in the market, or the management of a great factory or ironworks, or the business of a bill-broker. (Philip H. Wicksteed 1914 [1970]: 11)Marxism has very little of interest to say about the virtues of Icelandic cuisine in contrast to Bulgarian. Why should it? It is not some sort of cosmic philosophy along the lines of Rosicrucianism. It has had fairly little of interest to say about feminism either, partly because much of it has been conventionally patriarchal, but also because it is a restricted narrative which was never intended to be a Theory of Everything. (Terry Eagleton 1996: 111)